Penerapan Gaya Belajar Kolb, Honey And Mumford, Felder Silverman, Vark: Study Empiris pada Mahasiswa Pendidikan Teknologi Informasi IIB Darmajaya - Febriana, Annisa Arsya; Sari, Novita; Kumala, Dian Agustin Arta; Selfiyana, Reva; Hasibuan, Muhammad Said (Journal of Digital Literacy and Volunteering, 2025)
Learning styles play a significant role in shaping the learning process of each individual. This study employs a descriptive qualitative approach and involves 15 students from the Information Technology Education Study Program, consisting of 7 male and 8 female participants. Data were collected using four learning style questionnaires: VARK, Kolb’s Learning Style Inventory, Honey and Mumford’s Learning Styles Questionnaire, and the Felder-Silverman Learning Style Model. The objective of this research is to broaden instructional strategies by incorporating learning styles that align with students’ preferences. The findings underscore the importance of utilizing teaching methods that are congruent with students’ learning preferences to enhance academic achievement.